Cerebral infarction in centrum semiovale presenting with hemichorea: a case report and literature review - Yi, Jingjing; Zhang, Lingru; Zhang, Tao; Li, Jianfeng; Zhang, Yifan; Zhou, Meining (Frontiers in Neurology, 2023)
Hemichorea caused by cerebral infarction in the centrum semiovale is a rare condition that can often be misdiagnosed. In this case report, we present a rare case of a 66-year-old man who experienced involuntary movement in his left limbs due to acute cerebral infarction in the centrum semiovale. The patient did not have any obvious inducements for the hemichorea. In this case, the treatment approach followed the guidelines for treating acute cerebral infarction, combined with the use of dopamine receptor blockers. The involuntary movements gradually improved and completely remitted after 5 days of treatment, with no relapse within the following 6 months. To summarize, this case report highlights the rare occurrence of hemichorea caused by cerebral infarction in the centrum semiovale. Prompt recognition and appropriate treatment are essential to prevent misdiagnosis and ensure optimal management of the condition.